Coal gangue-based lightweight concrete material as well as preparation method and application thereof
By adding specific proportions of cement, fly ash, silica fume and composite foaming agent to the coal gangue foam concrete, and using modified fibers and hardening accelerators, the problems of low compressive strength and high water absorption are solved. Improves its application potential in building materials.
Patent Information
- Application Number
- CN202411320197.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
The existing coal gangue foam concrete materials have low compressive strength, uneven pore distribution, high water absorption and large shrinkage, which limit their application in building materials.
By mixing cement, gangue, fly ash, silicon fume, crack-resistant water reducer, reinforcement components and composite foaming agent in a specific proportion, a uniform structure is prepared, combining modified fibers and hardening promoters. , improve the compressive strength and stability of foam concrete and reduce water absorption.
It significantly improves the compressive strength of coal gangue foam concrete, reduces the formation of microcracks, reduces water absorption and dry shrinkage performance, improves the overall performance of the material, making it more suitable for use in building materials.
Smart Images

Figure CN119191789A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a gangue-based lightweight concrete material, a preparation method and application thereof. Background Art
[0002] Foam concrete has the advantages of sound insulation and light weight, and is widely used in the field of building materials. However, its scope of application is limited by its low strength due to its light weight, high water absorption rate due to its porosity, and large shrinkage.
[0003] Coal gangue is a by-product of coal mining and washing, with emissions accounting for about 10% to 15% of raw coal production. It is one of the largest industrial solid wastes emitted in my country. Its current treatment method is mostly open-air stacking, which not only occupies and destroys a large amount of land resources, but also the coal gangue is soaked in surface water and groundwater for a long time, with the risk of leaching of harmful elements, polluting the surrounding ecosystem and endangering humans through biological accumulation.
[0004] The application of coal gangue in foamed concrete can effectively utilize and process coal gangue. In the current existing technology, coal gangue foamed concrete is mainly used for mine filling. However, this kind of coal gangue foamed concrete material has the disadvantages of low compressive strength, uneven pore distribution, large shrinkage and water absorption. Therefore, it is of great significance to improve the performance of coal gangue foamed concrete. Summary of the invention
[0005] In order to improve the stability of bubbles in foam concrete paste and enhance the cement-gangue-bubble interface bonding strength, the present invention provides the following solutions:
[0006] The present invention provides a method for preparing a gangue-based lightweight concrete material, comprising the following steps:
[0007] The cement, coal gangue, fly ash, silica fume, anti-cracking water reducing agent, reinforcing component and water are mixed to prepare cement slurry; the composite foaming agent is diluted with water, and a foam with uniform structure is prepared by a compressed air foaming machine; the foam is added to the cement slurry, stirred and mixed evenly, and then poured into a mold, and after curing, a coal gangue-based lightweight concrete material is obtained.
[0008] In the above-mentioned method for preparing the gangue-based lightweight concrete material, the mass fractions of each raw material component are as follows:
[0009] 50-60 parts of cement, 25-35 parts of coal gangue, 5-15 parts of fly ash, 10-20 parts of silica fume, 0.5-1 part of anti-cracking water reducing agent, 2-5 parts of reinforcing component, 40-50 parts of water, and 2-3 parts of composite foaming agent.
[0010] In the method for preparing the above-mentioned coal gangue-based lightweight concrete material, the foam is prepared by diluting a composite foaming agent by 30 times with water.
[0011] In the preparation method of the above-mentioned coal gangue-based lightweight concrete material, the cement is PO42.5 ordinary Portland cement; the coal gangue is original coal gangue that is crushed and ball-milled to obtain a particle size of 0.075-0.3 mm; the fly ash is Class I or Class II fly ash; and the silicon content in the silica ash is ≥95%.
[0012] In the above-mentioned method for preparing the gangue-based lightweight concrete material, the anti-cracking water reducing agent is prepared by the following method:
[0013] Dissolve 50-100 parts of esterified macromonomer and 6-11 parts of unsaturated monomer in 18-33 parts of water to obtain solution A; dissolve 0.6-1.3 parts of initiator in 36-66 parts of water to obtain solution B; dissolve 0.6-1.3 parts of chain transfer agent in 28-55 parts of water to obtain solution C; add solution A, solution B and solution C dropwise to 6-11 parts of water, react at 50-80°C for 100-150 minutes, and naturally cool to room temperature after the reaction is completed; adjust the pH value to 6.5-7.0, then dialyze and dry to obtain an anti-cracking water reducer.
[0014] The above esterified macromonomer is prepared by the following method:
[0015] Mix 200-270 parts of enolate monomers, 20-28 parts of anhydride compounds, 6-10 parts of catalysts and 70-110 parts of organic solvents, heat to 130-170° C., stir and react for 70-800 minutes, and after the reaction is completed, cool to 70-85° C. to obtain an esterified macromonomer.
[0016] The above-mentioned enolate monomer is selected from one of polyvinyl alcohol, amino polyvinyl alcohol, and carboxyl polyvinyl alcohol; the above-mentioned acid anhydride compound is selected from one of succinic anhydride, acrylic anhydride, adipic anhydride, crotonic anhydride, isobutyric anhydride, isovaleric anhydride, itaconic anhydride, and glutaric anhydride; the above-mentioned catalyst is selected from one of p-toluenesulfonic acid, boric acid, acetic acid, and sulfuric acid; the above-mentioned organic solvent is selected from one of toluene, xylene, and N,N-dimethylformamide.
[0017] The unsaturated monomer is selected from at least one of itaconic acid, aconitic acid, maleic acid, acryloxypropionic acid, methacryloxypropionic acid, maleic anhydride, fumaric acid, crotonic acid, and β-(acryloxy)propionic acid; the initiator is selected from one or more of hydrogen peroxide, ammonium persulfate, sodium persulfate, and potassium persulfate; the chain transfer agent is selected from one or more of sodium methyl allyl sulfonate, hypophosphorous acid, sodium hypophosphite, potassium hypophosphite, sodium methyl sulfonate, sodium formate, and isopropanol; the pH is adjusted using at least one of NaOH, KOH, ammonia water, ethanolamine, diethanolamine, or triethanolamine, and the mass concentration of the regulator is selected from 10 to 30%.
[0018] In the preparation method of the above-mentioned coal gangue-based lightweight concrete material, the reinforcing component consists of a hardening accelerator and modified fibers; the mass ratio of the two is selected from 5-12:6-9.
[0019] The hardening accelerator is composed of calcium chloride and calcium formate; the mass ratio of the two is selected from 0.8-1:1-1.5.
[0020] The modified fiber is prepared by the following method:
[0021] The organic fiber is soaked in the modified polymer emulsion, taken out after soaking for 50 to 70 minutes, the calcium carbonate whisker is sprayed on the organic fiber, and hot air drying is performed at 70 to 90° C. to obtain the modified fiber.
[0022] The mass ratio of the modified polymer emulsion, calcium carbonate whisker and organic fiber is selected from 1-1.5:2-3:3-5.
[0023] The organic fiber is selected from one or more of polypropylene fiber, polyester fiber and polyvinyl alcohol fiber.
[0024] The modified polymer emulsion is prepared by the following method:
[0025] The polyacrylate, silane coupling agent and modified dimethyl silicone oil are mixed and stirred at room temperature for 30 to 45 minutes to obtain a modified polymer emulsion.
[0026] The mass ratio of the polyacrylate, the silane coupling agent and the modified dimethyl silicone oil is selected from 2-3:1-1.5:2-3.
[0027] The silane coupling agent is selected from one of vinyl trichlorosilane, vinyl triethoxysilane and vinyl triacetyl silane.
[0028] The modified dimethyl silicone oil is prepared by the following method:
[0029] Add Tween 60 and Spahn 60 to dimethyl silicone oil in sequence, stir evenly, then add water at 65-75°C, and then add carboxymethyl cellulose, stir to react, and obtain modified dimethyl silicone oil.
[0030] The mass ratio of the dimethyl silicone oil, Tween 60, Span 60, water and carboxymethyl cellulose is selected from 7-13: 1-1.5: 1-1.5: 70-130: 1-1.3.
[0031] In the above-mentioned method for preparing the gangue-based lightweight concrete material, the composite foaming agent is prepared by the following method:
[0032] The animal protein type foaming agent, Tween 20 and polyethylene glycol octylphenyl ether are mixed and stirred evenly to obtain a composite foaming agent.
[0033] The mass ratio of the animal protein foaming agent, Tween 20 and polyethylene glycol octylphenyl ether is selected from 10-20: 1-1.2: 1.2-1.5.
[0034] The invention provides a gangue-based lightweight concrete material prepared by the method.
[0035] The present invention provides application of the above-mentioned gangue-based lightweight concrete material in mine filling.
[0036] The beneficial effects of the present invention are:
[0037] (1) The present invention controls the particle size of coal gangue to be between 0.075 and 0.3 mm, which helps to improve the uniformity of coal gangue, improve the interface bonding between lightweight aggregate and powder, improve the compressive strength of foam concrete materials and reduce the generation of micro cracks in lightweight concrete materials.
[0038] (2) The present invention uses a mixture of Tween 20 and polyethylene glycol octylphenyl ether to maximize the effect of increasing viscosity. At the same time, the two interact with each other to achieve the effect of emulsifying protein, which can reduce the damage of the original interaction between animal protein foams, increase the thickness of the foam bubble wall, improve the pore structure of coal gangue foam concrete materials, increase the compressive strength of foam concrete materials, reduce its water absorption rate and improve shrinkage performance.
[0039] (3) The present invention utilizes highly emulsifiable Tween 60 and Spann 60 to emulsify dimethyl silicone oil by stirring evenly. The coordinated use of the two can improve the stability of the emulsion and promote the formation of the emulsion. The addition of carboxymethyl cellulose with good dispersibility can make the dimethyl silicone oil emulsified more evenly, improve the compatibility of dimethyl silicone oil and acrylic polymer emulsion, and use modified dimethyl silicone oil to modify acrylic emulsion, which can combine the advantages of the two and improve the water resistance of acrylic emulsion, reduce the water absorption rate of foamed concrete, and reduce the adverse effects on the compressive strength of foamed concrete.
[0040] (5) The polypropylene fiber is soaked in the modified polymer emulsion, which makes the fiber surface have the advantage of greater viscosity, which can enhance the fiber-cement interface bonding force. At the same time, due to the good hydrophobicity of the modified polymer emulsion, the fiber is interspersed between the bubble walls during the mixing process without causing the bubbles to burst, so that the pores inside the foam concrete are evenly reduced and the appearance of holes is greatly improved, which has a great improvement on the strength and water absorption performance of the foam concrete material.
[0041] (6) The calcium carbonate whiskers sprayed on the surface of the fiber impregnated with polymer emulsion exert micro-aggregate effect, pinning effect and nucleus effect at the plateau interface between the bubble walls, taking the fiber-bubble wall-paste interface as the nucleation site, and growing more hydrated calcium aluminate particles on the surface of the main products such as CSH and Ca(OH)2, making the foam concrete structure more compact. At the same time, combined with the hardening accelerator, it can maximize the compressive strength of the foam concrete material, make the foam concrete material harden faster, and prevent the foam from merging into interconnected pores, which causes defects in the compressive strength of the foam concrete material.
[0042] (7) The esterified polycarboxylic acid water reducer can improve the shrinkage performance and compressive strength of lightweight foam concrete materials. On the one hand, by increasing the contact angle between the pore wall and the pore solution, the surface tension of the pore solution is reduced, the decrease in relative humidity and the development of capillary negative pressure are delayed, thereby reducing the cracking caused by drying shrinkage and autogenous shrinkage, which is beneficial to reduce the shrinkage deformation of cement-based materials and improve the compressive strength of lightweight foam concrete materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The SEM analysis diagrams of the coal gangue foam concrete materials in Example 2, Comparative Example 1 and Comparative Example 2, wherein a is Example 2, b is Comparative Example 1, and c is Comparative Example 2;
[0044] Figure 2 The SEM pore analysis diagrams of the coal gangue foam concrete materials in Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5, wherein a is Example 2, b is Comparative Example 3, c is Comparative Example 4, and d is Comparative Example 5;
[0045] Figure 3 The pore structure distribution diagram of the SEM pore analysis diagram of the coal gangue foam concrete material described in Example 2, Comparative Example 3, Comparative Example 4 and Comparative Example 5 obtained by analyzing the software Image-Pro Plus 6.0, wherein a is Example 2, b is Comparative Example 3, c is Comparative Example 4, and d is Comparative Example 5;
[0046] Figure 4 The SEM analysis diagrams of the coal gangue foam concrete materials described in Example 2 and Comparative Example 11, wherein a is Example 2 and b is Comparative Example 11;
[0047] Figure 5 It is a surface tension analysis diagram of the water reducing agent in Example 2 and Comparative Example 15 measured by the pendant drop method of the surface tension meter, wherein a is Example 2 and b is Comparative Example 15. DETAILED DESCRIPTION
[0048] The present invention provides an anti-cracking water reducing agent, and the preparation method thereof is as follows:
[0049] 20 g of polyvinyl alcohol, 2 g of succinic anhydride, 1 g of toluenesulfonic acid and 9 g of toluene were placed in a four-necked flask (with a thermometer, a condenser, a water separator and a stirring rod), the temperature was raised to 150° C., and stirring was continued for 80 min. After the reaction was completed, the temperature was lowered to 75° C., and the impurities remaining in the flask were removed by a circulating water vacuum pump to obtain an esterified macromonomer;
[0050] 8 g of esterified macromonomer and 0.7 g of itaconic acid were dissolved in 0.3 g of water to obtain solution A; 0.1 g of hydrogen peroxide was dissolved in 4.3 g of water to obtain solution B; 0.1 g of sodium methyl allyl sulfonate was dissolved in 4.1 g of water to obtain solution C; solution A, solution B, and solution C were respectively added dropwise to a flask containing 0.8 g of deionized water (65° C.) within 180 min, and the constant temperature was maintained for 130 min after the addition was completed. After the reaction was completed, it was naturally cooled to room temperature; the pH value was adjusted to 7 with a mass concentration of 20% NaOH solution, and then the product was dialyzed for 70 h using a dialysis bag with a molecular weight cutoff of 6000 Da, and vacuum dried at 50° C. to constant weight to obtain a purified anti-cracking water reducer powder.
[0051] Other materials used in the present invention, if not otherwise stated, can be obtained through commercial channels. Other terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. The present invention is further described in detail below in conjunction with specific examples and with reference to data. The following examples are only for illustrating the present invention, and are not intended to limit the scope of the present invention in any way.
[0052] Example 1
[0053] The steps for preparing the gangue-based lightweight concrete material are as follows:
[0054] 500 g of cement, 250 g of coal gangue, 50 g of fly ash, 100 g of silica fume, 12 g of modified fiber, 5 g of anti-cracking water reducing agent, 5 g of calcium formate, 5 g of calcium chloride and 420 g of water were mixed to prepare cement slurry;
[0055] 20g of composite foaming agent was diluted 30 times with water, and uniformly structured foam was prepared by a compressed air foaming machine. The foam was added to the cement slurry, stirred and mixed evenly, and then poured into a mold. After 20h of initial curing and demolding, and after 80°C steam curing for 5d, a coal gangue-based lightweight concrete material was obtained.
[0056] In this embodiment, the particle size of the coal gangue is in the range of 0.075 to 0.3 mm.
[0057] In this embodiment, the modified fiber is prepared by the following method:
[0058] 12g of polypropylene fiber was soaked in 4g of modified polymer emulsion, and taken out after soaking for 1 hour. 9g of calcium carbonate whisker was sprayed on the polypropylene fiber soaked in polymer emulsion, and dried with hot air at 75°C to obtain modified fiber.
[0059] The modified polymer emulsion is prepared by the following method:
[0060] 20 g of polyacrylate, 10 g of vinyl triethoxysilane, and 20 g of modified dimethyl silicone oil were mixed, and stirred at room temperature for 40 min to obtain a modified polymer emulsion;
[0061] The modified dimethyl silicone oil is prepared by the following method:
[0062] Heat 8g of dimethyl silicone oil and 80g of deionized water to 70°C respectively for use; add 1g of Tween 60 and 1g of Spahn 60 to the dimethyl silicone oil in sequence, stir evenly in a beaker, slowly add 70°C deionized water to the beaker, and then add 1g of carboxymethyl cellulose, stir at 550r / min at room temperature for 120min to obtain modified dimethyl silicone oil.
[0063] In this embodiment, the composite foaming agent is prepared by the following method:
[0064] Mix 20 g of animal protein foaming agent, 1 g of Tween 20 and 1.2 g of polyethylene glycol octylphenyl ether, and stir evenly to prepare a composite foaming agent.
[0065] The animal protein foaming agent is purchased from the W-2 protein foaming agent produced by Hebei Enlin Building Materials Technology Co., Ltd.
[0066] Example 2
[0067] The steps for preparing the gangue-based lightweight concrete material are as follows:
[0068] 550 g of cement, 300 g of coal gangue, 100 g of fly ash, 150 g of silica fume, 15 g of modified fiber, 7 g of anti-cracking water reducing agent, 8 g of calcium formate, 8 g of calcium chloride and 460 g of water were mixed to prepare cement slurry;
[0069] 20g of composite foaming agent was diluted 30 times with water, and uniformly structured foam was prepared by a compressed air foaming machine. The foam was added to the cement slurry, stirred and mixed evenly, and then poured into a mold. After 20h of initial curing and demolding, and after 80°C steam curing for 5d, a coal gangue-based lightweight concrete material was obtained.
[0070] In this embodiment, the particle size of the coal gangue is in the range of 0.075 to 0.3 mm.
[0071] In this embodiment, the modified fiber is prepared by the following method:
[0072] 12g of polypropylene fiber was soaked in 4g of modified polymer emulsion, and taken out after soaking for 1 hour. 9g of calcium carbonate whisker was sprayed on the polypropylene fiber soaked in polymer emulsion, and dried with hot air at 75°C to obtain modified fiber.
[0073] The modified polymer emulsion is prepared by the following method:
[0074] 25 g of polyacrylate, 12 g of vinyl triethoxysilane, and 25 g of modified dimethyl silicone oil were mixed and stirred at room temperature for 40 min to obtain a modified polymer emulsion;
[0075] The modified dimethyl silicone oil is prepared by the following method:
[0076] Heat 10g of dimethyl silicone oil and 100g of deionized water to 70°C respectively for use; add 1.2g of Tween 60 and 1.2g of Spahn 60 to the dimethyl silicone oil in sequence, stir evenly in a beaker, slowly add 70°C deionized water to the beaker, and then add 1.1g of carboxymethyl cellulose, stir at 550r / min at room temperature for 120min to obtain modified dimethyl silicone oil.
[0077] In this embodiment, the composite foaming agent is prepared by the following method:
[0078] 20 g of animal protein foaming agent, 1.1 g of Tween 20 and 1.3 g of polyethylene glycol octylphenyl ether were mixed and stirred evenly to prepare a composite foaming agent.
[0079] The animal protein foaming agent is purchased from the W-2 protein foaming agent produced by Hebei Enlin Building Materials Technology Co., Ltd.
[0080] Example 3
[0081] The steps for preparing the gangue-based lightweight concrete material are as follows:
[0082] 600 g of cement, 350 g of coal gangue, 150 g of fly ash, 200 g of silica fume, 18 g of modified fiber, 9 g of anti-cracking water reducing agent, 12 g of calcium formate, 12 g of calcium chloride and 500 g of water were mixed to prepare cement slurry;
[0083] 20g of composite foaming agent was diluted 30 times with water, and uniformly structured foam was prepared by a compressed air foaming machine. The foam was added to the cement slurry, stirred and mixed evenly, and then poured into a mold. After 20h of initial curing and demolding, and after 80°C steam curing for 5d, a coal gangue-based lightweight concrete material was obtained.
[0084] In this embodiment, the particle size of the coal gangue is in the range of 0.075 to 0.3 mm.
[0085] In this embodiment, the modified fiber is prepared by the following method:
[0086] 12g of polypropylene fiber was soaked in 4g of modified polymer emulsion, and taken out after soaking for 1 hour. 9g of calcium carbonate whisker was sprayed on the polypropylene fiber soaked in polymer emulsion, and dried with hot air at 75°C to obtain modified fiber.
[0087] The modified polymer emulsion is prepared by the following method:
[0088] 30 g of polyacrylate, 14 g of vinyl triethoxysilane, and 30 g of modified dimethyl silicone oil were mixed, and stirred at room temperature for 40 min to obtain a modified polymer emulsion;
[0089] The modified dimethyl silicone oil is prepared by the following method:
[0090] Heat 13 g of dimethyl silicone oil and 130 g of deionized water to 70°C for use; add 1.4 g of Tween 60 and 1.4 g of Spam 60 to the dimethyl silicone oil in sequence and stir evenly in a beaker; slowly add 70°C deionized water to the beaker, and then add 1.2 g of carboxymethyl cellulose; stir at 550 r / min at room temperature for 120 min to obtain modified dimethyl silicone oil.
[0091] In this embodiment, the composite foaming agent is prepared by the following method:
[0092] 20 g of animal protein foaming agent, 1.2 g of Tween 20 and 1.5 g of polyethylene glycol octylphenyl ether were mixed and stirred evenly to prepare a composite foaming agent.
[0093] The animal protein foaming agent is purchased from the W-2 protein foaming agent produced by Hebei Enlin Building Materials Technology Co., Ltd.
[0094] Comparative Example 1
[0095] This comparative example prepares a coal gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that the particle size of the coal gangue is less than 0.075 mm. The other steps are the same as those in Example 2.
[0096] Comparative Example 2
[0097] This comparative example prepares a coal gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that the particle size of the coal gangue is in the range of 0.3 mm to 0.6 mm. The other steps are the same as those in Example 2.
[0098] Comparative Example 3
[0099] This comparative example prepares a gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that the preparation method of the composite foaming agent is different; wherein, when preparing the composite foaming agent, Tween 20 is not added. The other steps are the same as those in Example 2.
[0100] In this comparative example, the composite foaming agent is prepared by the following method:
[0101] 20 g of animal protein foaming agent and 1.3 g of polyethylene glycol octylphenyl ether were mixed and stirred evenly to obtain a composite foaming agent.
[0102] The animal protein foaming agent is purchased from the W-2 protein foaming agent produced by Hebei Enlin Building Materials Technology Co., Ltd.
[0103] Comparative Example 4
[0104] This comparative example prepares a gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that the preparation method of the composite foaming agent is different; wherein, when preparing the composite foaming agent, polyethylene glycol octyl phenyl ether is not added. The other steps are the same as those of Example 2.
[0105] In this comparative example, the composite foaming agent is prepared by the following method:
[0106] Mix 20 g of animal protein foaming agent and 1.1 g of Tween 20, and stir evenly to obtain a composite foaming agent.
[0107] The animal protein foaming agent is purchased from the W-2 protein foaming agent produced by Hebei Enlin Building Materials Technology Co., Ltd.
[0108] Comparative Example 5
[0109] This comparative example prepares a gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that an animal protein-based foaming agent is directly used for foaming, and Tween 20 and polyethylene glycol octylphenyl ether are not added. The other steps are the same as those in Example 2.
[0110] The animal protein foaming agent is purchased from the W-2 protein foaming agent produced by Hebei Enlin Building Materials Technology Co., Ltd.
[0111] Comparative Example 6
[0112] This comparative example prepares a coal gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that the preparation method of the modified fiber is different; wherein, when preparing the modified dimethyl silicone oil, Tween 60 is not added. The other steps are the same as those in Example 2.
[0113] In this comparative example, the modified fiber is prepared by the following method:
[0114] 12g of polypropylene fiber was soaked in 4g of modified polymer emulsion, and taken out after soaking for 1 hour. 9g of calcium carbonate whisker was sprayed on the polypropylene fiber soaked in polymer emulsion, and dried with hot air at 75°C to obtain modified fiber.
[0115] The modified polymer emulsion is prepared by the following method:
[0116] 25 g of polyacrylate, 12 g of silane coupling agent, and 25 g of modified dimethyl silicone oil were mixed, and stirred at room temperature for 40 min to obtain a modified polymer emulsion;
[0117] The modified dimethyl silicone oil is prepared by the following method:
[0118] Heat 10g of dimethyl silicone oil and 100g of deionized water to 70°C respectively for use; add 1.2g of Span 60 to the dimethyl silicone oil and stir evenly in a beaker, slowly add 70°C deionized water to the beaker, and then add 1.1g of carboxymethyl cellulose, stir at 550r / min at room temperature for 120min to obtain modified dimethyl silicone oil.
[0119] Comparative Example 7
[0120] This comparative example prepares a gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that the preparation method of the modified fiber is different; wherein, when preparing the modified dimethyl silicone oil, Span 60 is not added. The other steps are the same as those in Example 2.
[0121] In this comparative example, the modified fiber is prepared by the following method:
[0122] 12g of polypropylene fiber was soaked in 4g of modified polymer emulsion, and taken out after soaking for 1 hour. 9g of calcium carbonate whisker was sprayed on the polypropylene fiber soaked in polymer emulsion, and dried with hot air at 75°C to obtain modified fiber.
[0123] The modified polymer emulsion is prepared by the following method:
[0124] 25 g of polyacrylate, 12 g of silane coupling agent, and 25 g of modified dimethyl silicone oil were mixed, and stirred at room temperature for 40 min to obtain a modified polymer emulsion;
[0125] The modified dimethyl silicone oil is prepared by the following method:
[0126] Heat 10g of dimethyl silicone oil and 100g of deionized water to 70°C respectively for use; add 1.2g of Tween 60 to the dimethyl silicone oil and stir evenly in a beaker, slowly add 70°C deionized water to the beaker, and then add 1.1g of carboxymethyl cellulose, stir at 550r / min at room temperature for 120min to obtain modified dimethyl silicone oil.
[0127] Comparative Example 8
[0128] This comparative example prepares a coal gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that the preparation method of the modified fiber is different; wherein, when preparing the modified dimethyl silicone oil, no carboxymethyl cellulose is added. The other steps are the same as those of Example 2.
[0129] In this comparative example, the modified fiber is prepared by the following method:
[0130] 12g of polypropylene fiber was soaked in 4g of modified polymer emulsion, and taken out after soaking for 1 hour. 9g of calcium carbonate whisker was sprayed on the polypropylene fiber soaked in polymer emulsion, and dried with hot air at 75°C to obtain modified fiber.
[0131] The modified polymer emulsion is prepared by the following method:
[0132] 25 g of polyacrylate, 12 g of silane coupling agent, and 25 g of modified dimethyl silicone oil were mixed, and stirred at room temperature for 40 min to obtain a modified polymer emulsion;
[0133] The modified dimethyl silicone oil is prepared by the following method:
[0134] Heat 10 g of dimethyl silicone oil and 100 g of deionized water to 70°C for use; add 1.2 g of Tween 60 and 1.2 g of Spahn 60 to the dimethyl silicone oil in sequence, stir evenly in a beaker, slowly add 70°C deionized water to the beaker, stir at 550 r / min for 120 min at room temperature to obtain modified dimethyl silicone oil.
[0135] Comparative Example 9
[0136] This comparative example prepares a coal gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that, in the process of preparing the modified fiber, modified dimethyl silicone oil is not added to the modified polymer emulsion. The other steps are the same as those in Example 2.
[0137] In this comparative example, the modified fiber is prepared by the following method:
[0138] 12g of polypropylene fiber was soaked in 4g of modified polymer emulsion, and taken out after soaking for 1 hour. 9g of calcium carbonate whisker was sprayed on the polypropylene fiber soaked in polymer emulsion, and dried with hot air at 75°C to obtain modified fiber.
[0139] In this comparative example, the modified polymer emulsion is prepared by the following method:
[0140] 25 g of polyacrylate and 12 g of silane coupling agent were mixed and stirred at room temperature for 40 min to obtain a modified polymer emulsion.
[0141] Comparative Example 10
[0142] This comparative example prepares a coal gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that, in the process of preparing the modified fiber, the modified polymer emulsion is replaced by modified dimethyl silicone oil. The other steps are the same as those in Example 2.
[0143] In this comparative example, the modified fiber is prepared by the following method:
[0144] 12g of polypropylene fiber was soaked in 4g of modified dimethyl silicone oil, and taken out after soaking for 1 hour. 9g of calcium carbonate whisker was sprayed on the polypropylene fiber soaked in the polymer emulsion, and hot air dried at 75°C to obtain modified fiber.
[0145] The modified dimethyl silicone oil is prepared by the following method:
[0146] Heat 10g of dimethyl silicone oil and 100g of deionized water to 70°C respectively for use; add 1.2g of Tween 60 and 1.2g of Spahn 60 to the dimethyl silicone oil in sequence, stir evenly in a beaker, slowly add 70°C deionized water to the beaker, and then add 1.1g of carboxymethyl cellulose, stir at 550r / min at room temperature for 120min to obtain modified dimethyl silicone oil.
[0147] Comparative Example 11
[0148] This comparative example prepares a coal gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that the preparation method of the modified fiber is different; wherein, when preparing the modified fiber, no calcium carbonate whisker is added. The other steps are the same as those of Example 2.
[0149] In this comparative example, the modified fiber is prepared by the following method:
[0150] 12g of polypropylene fiber was soaked in 4g of modified polymer emulsion, taken out after soaking for 1h, and dried with hot air at 75℃ to obtain modified fiber;
[0151] The modified polymer emulsion is prepared by the following method:
[0152] 25 g of polyacrylate, 12 g of silane coupling agent, and 25 g of modified dimethyl silicone oil were mixed, and stirred at room temperature for 40 min to obtain a modified polymer emulsion;
[0153] The modified dimethyl silicone oil is prepared by the following method:
[0154] Heat 10g of dimethyl silicone oil and 100g of deionized water to 70°C respectively for use; add 1.2g of Tween 60 and 1.2g of Spahn 60 to the dimethyl silicone oil in sequence, stir evenly in a beaker, slowly add 70°C deionized water to the beaker, and then add 1.1g of carboxymethyl cellulose, stir at 550r / min at room temperature for 120min to obtain modified dimethyl silicone oil.
[0155] Comparative Example 12
[0156] This comparative example prepares a coal gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that no modified fiber is added. The other steps are the same as those in Example 2.
[0157] Comparative Example 13
[0158] This comparative example prepares a coal gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that no anti-cracking water reducing agent is added. The other steps are the same as those in Example 2.
[0159] Comparative Example 14
[0160] This comparative example prepares a coal gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that calcium chloride, calcium formate and modified fiber are not added. The other steps are the same as those in Example 2.
[0161] Comparative Example 15
[0162] This comparative example prepares a coal gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that a commercially available polycarboxylate water reducer is used instead of an anti-cracking water reducer. The other steps are the same as those in Example 2.
[0163] The polycarboxylate water reducer was purchased from Langfang Longteng New Materials Co., Ltd., model number PC-1050.
[0164] Comparative Example 16
[0165] This comparative example prepares a coal gangue-based lightweight concrete material, which is different from the above-mentioned Example 2 in that commercially available polypropylene fibers are used instead of modified fibers. The other steps are the same as those in Example 2.
[0166] The polypropylene fiber was purchased from Tuoda New Materials Technology Industry Group Co., Ltd., model TD-YUJ.
[0167] Concrete performance testing
[0168] The 28d compressive strength of the above-mentioned implementation cases was tested according to JG / T 169-2016 "General Technical Requirements for Lightweight Strips for Building Partition Walls". The thermal conductivity of the above-mentioned implementation cases was measured and calculated according to GB / T 13475-2008 "Determination and Calibration of Adiabatic Steady-State Heat Transfer Properties and Guarded Hot Box Method". The water absorption and shrinkage of the above-mentioned implementation cases were tested according to JG / T 266-2011 "Foamed Concrete".
[0169] The test results are shown in Table 1:
[0170] Table 1 Properties of concrete prepared in each implementation case
[0171]
[0172]
[0173] By comparing Example 1, Example 2, Example 3 with Comparative Example 1 and Comparative Example 2, and combining Figure 1 It can be seen that controlling the particle size of coal gangue between 0.075 and 0.3 mm helps to improve the uniformity of coal gangue and improve the interface bonding between lightweight aggregate and powder. In Example 2, the particle size of coal gangue is controlled to be between 0.075 and 0.3 mm, and the foamed concrete produces more hydration products, which react with the cement clinker hydration products in a secondary reaction, consume Ca(OH)2 and generate a large area of CSH gel and AFt crystals, and some Ca(OH)2 crystals are wrapped by CSH gel and AFt, thereby improving the compressive strength of the foamed concrete material. In Comparative Example 1, the coal gangue particles are too large and have low activity. A large amount of Ca(OH)2 is not consumed when participating in secondary hydration, resulting in a decrease in the compressive strength of the foamed concrete and an increase in water absorption. In Comparative Example 2, the coal gangue particles are too small, and the overall structure of the foamed concrete material is loose, resulting in a decrease in its compressive strength and even microcracks.
[0174] By comparing Example 2 with Comparative Example 3, Comparative Example 4 and Comparative Example 5, and combining Figure 2 , Figure 3 It can be seen that the mixed use of Tween 20 and polyethylene glycol octylphenyl ether can maximize the effect of increasing foam viscosity. At the same time, the interaction between the two can achieve the effect of emulsifying protein, reduce the destruction of the original interaction between animal protein foams, increase the thickness of foam bubble walls, increase the proportion of small pores less than 300μm, improve foam stability, optimize the pore structure of foam concrete, and achieve the purpose of improving the compressive strength of foam concrete materials and reducing their water absorption and thermal conductivity.
[0175] From the comparison between Example 2 and Comparative Examples 6, 7, 8, 9 and 10, it can be seen that the synergistic effect of highly emulsifiable Tween 60 and Span 60 on dimethyl silicone oil can improve the stability of the emulsion and promote the formation of the emulsion, and carboxymethyl cellulose makes the dimethyl silicone oil emulsified more uniformly; the use of silicone to modify the acrylic emulsion can combine the advantages of the two and improve the water resistance of the acrylic emulsion, thereby making the bubble film less susceptible to water erosion and causing rupture and merging, thereby improving the stability of the bubbles in the cement slurry, improving the compressive strength of the foamed concrete, while reducing the water absorption rate of the foamed concrete material and improving the drying shrinkage performance.
[0176] From the comparison between Example 2 and Comparative Examples 12 and 14, it can be seen that the polypropylene fiber is impregnated with the modified polymer emulsion, so that the fiber surface has the advantage of greater viscosity, which can enhance the fiber-cement interface bonding force. At the same time, due to the good hydrophobicity of the modified polymer emulsion, the fiber is interspersed between the bubble walls during the stirring process without causing the bubble to burst, so that the pores inside the foam concrete are evenly reduced, and the appearance of holes is improved, thereby improving the compressive strength of the foam concrete and reducing its water absorption rate.
[0177] By comparing Example 2 with Comparative Example 11 and Comparative Example 16, and combining Figure 4 It can be seen that the calcium carbonate whiskers sprayed on the surface of the fiber impregnated with polymer emulsion exert micro-aggregate effect, pinning effect and nucleus effect at the plateau interface between the bubble walls. Their high specific surface area increases the contact area with water, accelerates the hydration rate of C3S, and grows more hydrated calcium aluminate particles on the surface of main products such as CSH and Ca(OH)2, making the foam concrete structure denser. At the same time, combined with CaCl2 and Ca(HCOO)2 in the hardening accelerator, it can maximize the early strength of the foam concrete material, make it harden quickly, and prevent the foam from merging into connected pores to cause mold collapse.
[0178] By comparing Example 2 with Comparative Example 13 and Comparative Example 15, and combining Figure 5 It can be seen that the esterified water reducer can improve the shrinkage performance and compressive strength of coal gangue foam concrete materials. By reducing the surface tension of the pore solution, delaying the decline in relative humidity and the development of capillary negative pressure, the stability of bubbles in the foam concrete material is improved, and the cracking caused by drying shrinkage and autogenous shrinkage is reduced, which is beneficial to improving the compressive strength of coal gangue foam concrete materials and reducing shrinkage deformation.
[0179] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a gangue-based lightweight concrete material, characterized in that: The steps include: The cement, coal gangue, fly ash, silica fume, anti-cracking water reducing agent, reinforcing component and water are mixed to prepare cement slurry; the composite foaming agent is diluted with water, and a foam with uniform structure is prepared by a compressed air foaming machine; the foam is added to the cement slurry, stirred and mixed evenly, and then poured into a mold, and after curing, a coal gangue-based lightweight concrete material is obtained.
2. The preparation method according to claim 1, characterized in that: The mass fractions of each raw material component are as follows: 50-60 parts of cement, 25-35 parts of coal gangue, 5-15 parts of fly ash, 10-20 parts of silica fume, 0.5-1 part of anti-cracking water reducing agent, 2-5 parts of reinforcing component, 40-50 parts of water, and 2-3 parts of composite foaming agent.
3. The preparation method according to claim 1, characterized in that: The cement is PO42.5 ordinary Portland cement; the coal gangue is original coal gangue obtained by crushing and ball milling to obtain a particle size of 0.075-0.3mm; the fly ash is grade I or grade II fly ash; the silicon content in the silica ash is ≥95%.
4. The preparation method according to claim 1, characterized in that: The anti-cracking water reducing agent is prepared by the following method: Dissolve 50-100 parts of esterified macromonomer and 6-11 parts of unsaturated monomer in 18-33 parts of water to obtain solution A; dissolve 0.6-1.3 parts of initiator in 36-66 parts of water to obtain solution B; dissolve 0.6-1.3 parts of chain transfer agent in 28-55 parts of water to obtain solution C; add solution A, solution B and solution C dropwise to 6-11 parts of water, react at 50-80° C. for 100-150 minutes, and naturally cool to room temperature after the reaction is completed; adjust the pH value to 6.5-7.0, then dialyze and dry to obtain an anti-cracking water reducer; The esterification macromonomer is prepared by the following method: 200-270 parts of enolate monomer, 20-28 parts of anhydride compound, 6-10 parts of catalyst and 70-110 parts of organic solvent are mixed, the temperature is raised to 130-170° C., and the mixture is stirred for reaction for 70-800 minutes. After the reaction is completed, the temperature is lowered to 70-85° C. to obtain an esterified macromonomer; The enolate monomer is selected from one of polyvinyl alcohol, amino polyvinyl alcohol, and carboxyl polyvinyl alcohol; the acid anhydride compound is selected from one of succinic anhydride, acrylic anhydride, adipic anhydride, crotonic anhydride, isobutyric anhydride, isovaleric anhydride, itaconic anhydride, and glutaric anhydride; the catalyst is selected from one of p-toluenesulfonic acid, boric acid, acetic acid, and sulfuric acid; the organic solvent is selected from one of toluene, xylene, and N,N-dimethylformamide; The unsaturated monomer is selected from at least one of itaconic acid, aconitic acid, maleic acid, acryloxypropionic acid, methacryloxypropionic acid, maleic anhydride, fumaric acid, crotonic acid, and β-(acryloxy)propionic acid; the initiator is selected from one or more of hydrogen peroxide, ammonium persulfate, sodium persulfate, and potassium persulfate; the chain transfer agent is selected from one or more of sodium methyl allyl sulfonate, hypophosphorous acid, sodium hypophosphite, potassium hypophosphite, sodium methyl sulfonate, sodium formate, and isopropanol; the pH is adjusted using at least one of NaOH, KOH, ammonia water, ethanolamine, diethanolamine, or triethanolamine, and the mass concentration of the regulator is selected from 10 to 30%.
5. The preparation method according to claim 1, characterized in that: The reinforcing component consists of a hardening accelerator and modified fibers, the mass ratio of which is selected from 5 to 12: 6 to 9; the hardening accelerator consists of calcium chloride and calcium formate, the mass ratio of which is selected from 0.8 to 1: 1 to 1.
5.
6. The preparation method according to claim 1, characterized in that: The modified fiber is prepared by the following method: The organic fiber is soaked in the modified polymer emulsion, taken out after soaking for 50 to 70 minutes, and the calcium carbonate whisker is sprayed on the organic fiber, and hot air dried at 70 to 90° C. to obtain the modified fiber; The mass ratio of the modified polymer emulsion, calcium carbonate whisker and organic fiber is selected from 1-1.5:2-3:3-5; the organic fiber is selected from one or more of polypropylene fiber, polyester fiber and polyvinyl alcohol fiber.
7. The preparation method according to claim 1, characterized in that: The modified polymer emulsion is prepared by the following method: Mixing polyacrylate, silane coupling agent and modified dimethyl silicone oil and stirring at room temperature for 30 to 45 minutes to obtain a modified polymer emulsion; The mass ratio of the polyacrylate, the silane coupling agent, and the modified dimethyl silicone oil is selected from 2-3:1-1.5:2-3; the silane coupling agent is selected from one of vinyl trichlorosilane, vinyl triethoxysilane, and vinyl triacetyl silane; The modified dimethyl silicone oil is prepared by the following method: Add Tween 60 and Spahn 60 to dimethyl silicone oil in sequence, stir evenly, then add water at 65-75°C, then add carboxymethyl cellulose, stir and react to obtain modified dimethyl silicone oil; The mass ratio of the dimethyl silicone oil, Tween 60, Span 60, water and carboxymethyl cellulose is selected from 7-13:1-1.5:1-1.5:70-130:1-1.
3.
8. The preparation method according to claim 1, characterized in that: The composite foaming agent is prepared by the following method: Animal protein foaming agent, Tween 20 and polyethylene glycol octyl phenyl ether are mixed and stirred evenly to obtain a composite foaming agent; the mass ratio of the animal protein foaming agent, Tween 20 and polyethylene glycol octyl phenyl ether is selected from 10-20:1-1.2:1.2-1.
5.
9. Gangue-based lightweight concrete material prepared by the method according to any one of claims 1 to 8.
10. Use of the gangue-based lightweight concrete material according to claim 9 in mine filling.
Citation Information
Cited By
Coal gangue-based porous artificial soil as well as preparation method and application thereof
CN120113562A
Low-thermal-conductivity concrete and preparation method thereof
CN121248244A
Low thermal conductivity concrete and method for producing same
CN121248244B
